An analysis of the dissipation of pharmaceuticals under thirteen different soil conditions - Kodešová, Radka; Kočárek, Martin; Klement, Aleš; Golovko, Oksana; Koba, Olga; Fér, Miroslav; Nikodem, Antonín; Vondráčková, Lenka; Jakšík, Ondřej; Grabic, Roman (The Science of the total environment, 2016)
The presence of human and veterinary pharmaceuticals in the environment is recognized as a potential threat. Pharmaceuticals have the potential to contaminate soils and consequently surface and groundwater. Knowledge of contaminant behavior (e.g., sorption onto soil particles and degradation) is essential when assessing contaminant migration in the soil and groundwater environment. We evaluated the dissipation half-lives of 7 pharmaceuticals in 13 soils. The data were evaluated relative to the soil properties and the Freundlich sorption coefficients reported in our previous study. Of the tested pharmaceuticals, carbamazepine had the greatest persistence (which was mostly stable), followed by clarithromycin, trimethoprim, metoprolol, clindamycin, sulfamethoxazole and atenolol. Pharmaceutical persistence in soils was mostly dependent on the soil-type conditions. In general, lower average dissipation half-lives and variability (i.e., trimethoprim, sulfamethoxazole, clindamycin, metoprolol and atenolol) were found in soils of better quality (well-developed structure, high nutrition content etc.), and thus, probably better microbial conditions (i.e., Chernozems), than in lower quality soil (Cambisols). The impact of the compound sorption affinity onto soil particles on their dissipation rate was mostly negligible. Although there was a positive correlation between compound dissipation half-life and Freundlich sorption coefficient for clindamycin (R=0.604, p<0.05) and sulfamethoxazole (R=0.822, p<0.01), the half-life of sulfamethoxazole also decreased under better soil-type conditions. Based on the calculated dissipation and sorption data, carbamazepine would be expected to have the greatest potential to migrate in the soil water environment, followed by sulfamethoxazole, trimethoprim and metoprolol. The transport of clindamycin, clarithromycin and atenolol through the vadose zone seems less probable.
Keywords: Ionizable compounds; Carbamazepine; Biodegradation, Environmental; Dissipation half-life; Half-Life; sulfamethoxazol; Sulfamethoxazole; Models, Chemical; látky znečišťující půdu; Trimethoprim; Soil; Soil Pollutants; Soil properties; Soil types; karbamazepin; Pharmaceuticals; půda; chemické modely; poločas; trimethoprim; biodegradace